A new genus of millipede (Diplopoda: Polydesmida: Dalodesmidae) from Tasmania with a pseudo-articulated gonopod telopodite - Mesibov, Robert (Zootaxa, 2005)
Ginglymodesmus tasmanianus n. gen., n. sp., G. penelopae n. sp. and G. sumac n. sp. are described from northwest Tasmania, Australia. The three species have long, slender gonopod telopodites divided into proximal and distal sections, with the distal section pivoting around a hinge-like structure which appears to differ from the typical joint in an arthropod leg.